Design of Compact Reconfigurable Antenna Array for WLAN Applications - Qasaymeh, Yazeed M. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
In this communication, a compact design of a reconfigurable antenna array operating in the band IEEE 802.11a is presented. The proposed antenna array contains four radiating elements excited by a hybrid parallel-series-feed network. The hybrid feed technique is used to avoid the main beam squint due to frequency changes compared to series and parallel array feed topologies. Each of the four radiating elements consists of straight narrow strip inductor in parallel with an interdigital capacitor. The antenna resonant frequency is electronically controlled by placing PIN diodes switches at the resonant element’s inputs. The antenna permits reconfigurable switching frequency bands between 5.25 and 5.82 GHz. The results of the return loss and pattern radiation are shown. The size of the whole antenna structure is about 64 × 18 mm2 and can potentially be used in wireless systems.